Comparative computational analysis of the selection of battery energy storage for civil objects and parking with photovoltaic plants - Zinkevych, Petro; Baliuta, Serhii; Kuievda, Yulia (My University, 2022)
Energy production from PPS has a number of advantages and disadvantages. One of the disadvantages is that PPS does not produce electricity at night, so they cannot support the load of consumers. To solve the problem of stability of electricity supply at night battery energy storage (BES) are used [1]. BES in combination with a solar power plant is called a battery energy storage system (BESS). This system absorbs and releases energy in different periods. There is no doubt that the additional investment and operating costs of BESS will affect the cost-effectiveness of the PPS.
Keywords: BESS; solar energy storage; solar power plants; накопичення сонячної енергії; сонячні електростанції; кафедра електропостачання і енергоменеджменту